2018
DOI: 10.1002/bjs5.50107
|View full text |Cite
|
Sign up to set email alerts
|

International benchmarking in oesophageal and gastric cancer surgery

Abstract: BackgroundBenchmarking on an international level might lead to improved outcomes at a national level. The aim of this study was to compare treatment and surgical outcome data from the Swedish National Register for Oesophageal and Gastric Cancer (NREV) and the Dutch Upper Gastrointestinal Cancer Audit (DUCA).MethodsAll patients with primary oesophageal or gastric cancer who underwent a resection and were registered in NREV or DUCA between 2012 and 2014 were included. Differences in 30‐day mortality were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…Between 2011 and 2016, of all gastrectomies for gastric cancer with curative intent, in 9–13% the tumors were incompletely removed 3. This number corresponds with other European outcome registries 4,5. The British National Oesophago-Gastric Cancer Audit (NOGCA) reported that up to 29% of the gastrectomies performed in individual hospitals had tumor-positive margins 5.…”
supporting
confidence: 62%
“…Between 2011 and 2016, of all gastrectomies for gastric cancer with curative intent, in 9–13% the tumors were incompletely removed 3. This number corresponds with other European outcome registries 4,5. The British National Oesophago-Gastric Cancer Audit (NOGCA) reported that up to 29% of the gastrectomies performed in individual hospitals had tumor-positive margins 5.…”
supporting
confidence: 62%
“…The results of the DUCA were compared with the results of the Swedish NREV (Nationellt Kvalitetsregister matstrups-och magsäckscancer). 20 However, the results of the registries at that time were not standardized, which makes comparison not really reliable.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a steadily growing proportion of Swedish patients receiving preoperative oncological treatment, albeit to a lesser extent than in other countries. 3 Both 30- and 90-day mortality rates for resections of esophageal/GEJ cancer remain unchanged, whereas a decline in the corresponding figures for gastric cancer was seen. This could, in part, be explained by the process of centralization of these complex procedures in Sweden during this period, most notably accentuated for by gastric cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Assuming high validity of the data entered into the register, comprehensive comparisons can be conducted between regions within a country or between countries. 2 , 3 Resection rates for both esophageal and gastric cancer have decreased in Sweden during the years 2007–2016 ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%